(untitled) (Konturen, 2014)
Within the context of an inquiry into the borders between human and animal, this essay considers the question of the humanity–or animality–of children as they are depicted in nineteenth-century German literature and elsewhere. Defining nineteenth-century literary "humanity" as a regulating, domesticating, bourgeoisification, I examine E.T.A. Hoffmann’s Der Sandmann and Heinrich Hoffmann’s Der Struwwelpeter, and follow the sins of omission (Sandmann) and comission (Struwwelpeter) that seem to authorize the inhuman treatment of children. Nathanael, Coppelius’s "little beast," is reduced both to beast and automaton/wooden doll and ultimately destroyed in E.T.A. Hoffmann’s adult novella. Twenty-nine years later, the young protagonists of Heinrich Hoffmann’s children’s book suffer gruesome punishments for their willful transgression of bourgeois norms and domestic law. But the children’s rhymes produced in 1845 have a revolutionary flavor that underscores the subject’s freedom.